Interpretación de la dimensión educativa de la pastoral juvenil en tres obras de San Agustín - Altamirano Molina, Marcelo Bolíbar (2014)
ABSTRACT The "Interpretation of the educational dimension of youth ministry in three works of St. Augustine," thesis is to analyze the educational and pastoral Augustine of Hippo budgets, their relationship with the educational and pastoral practices in Ecuador and approaches and perspectives that establish a model of youth ministry who carry an improved development of the youth groups.